Quality, language, subdiscipline and promotion were associated with article accesses on Physiotherapy Evidence Database (PEDro). Issue 1 (March 2018) - Yamato, Tiê P.; Arora, Mohit; Stevens, Matthew L.; Elkins, Mark R.; Moseley, Anne M.
Abstract: Objective: To quantify the relationship between the number of times articles are accessed on the Physiotherapy Evidence Database (PEDro) and the article characteristics. A secondary aim was to examine the relationship between accesses and the number of citations of articles. Method: The study was conducted to derive prediction models for the number of accesses of articles indexed on PEDro from factors that may influence an article's accesses. All articles available on PEDro from August 2014 to January 2015 were included. We extracted variables relating to the algorithm used to present PEDro search results (research design, year of publication, PEDro score, source of systematic review (Cochrane or non-Cochrane)) plus language, subdiscipline of physiotherapy, and whether articles were promoted to PEDro users. Three predictive models were examined using multiple regression analysis. Citation and journal impact factor were downloaded. Results: There were 29, 313 articles indexed in this period. We identified seven factors that predicted the number of accesses. More accesses were noted for factors related to the algorithm used to present PEDro search results (synthesis research (i.e., guidelines and reviews), recent articles, Cochrane reviews, and higher PEDro score) plus publication in English and being promoted to PEDro users. The musculoskeletal, neurology, orthopaedics, sports, and paediatrics subdisciplines were associated with more accesses. We also found that there was no association between number of accesses and citations. Conclusion: The number of times an article is accessed on PEDro is partly predicted by how condensed and high quality the evidence it contains is.